EVALUATION OF THREE MEDICINAL PLANT EXTRACTS AGAINST PLASMODIUM FALCIPARUM AND SELECTED MICROGANISMS - Falodun, Abiodun; Imieje, Vincent; Erharuyi, Osayewenre; Ahomafor, Joy; Jacob, Melissa R; Khan, Shabana I; Hamann, Mark T (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: A great revival of scientific interests in drug discovery has been witnessed in recent years from medicinal plants for health maintenance. The aim of this work was to investigate three Nigerian medicinal plants collected in Nigeria for their in vitro antiplasmodial and antimicrobial activities. Materials and Methods: Extracts obtained from parts of Persea americana, Jatropha podagrica and Picralima nitida and their fractions were evaluated for in vitro antiprotozoal and antimicrobial activity. Result: The methanol extract of P. nitida demonstrated activity against chloroquine-sensitive and chloroquine-resistant P. falciparum clones with IC50 values of 6.3 and 6.0 µg/mL, respectively. Methanol and chloroform extracts of P. americana seed showed antifungal activity against Cryptococcus neoformans IC50 less than 8 and 8.211 µg/mL respectively. Finally, the petroleum ether extract of P. americana had activity against methicillin-resistant Staphylococcus aureus (MRSA) with an IC50 value of 8.7 µg/mL. Conclusion: The study revealed the antibacterial and antiplasmodial activities of the plants extracts at the tested concentrations.